Socio-community practices as bridges of encounter between knowledge (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
Within the framework of Community Practices and the Field of Practices, we initiate learning spaces, among bakers, students and teachers, in the search for practical and theoretical knowledge; academic and empirical, with concrete actions for the reco-very, assessment and visibility of the work in artisan brick kilns. Likewise, we coordinate this meeting space with the Technical Secondary School to generate a meaningful educational exchange for students where academic and popular knowledge are combined with interdisciplinary knowledge of secondary education in order to express its practical application in the community.
Keywords: practices; university extension; knowledge; bakers